Integrating Philanthropic Values in Islamic Religious Education Learning Through Project-Based Learning Methods - Aziz Muslim; Salihou Hamadou; Eka Safitri (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2026)
The Project-Based Learning (PjBL) approach in Islamic Religious Education (PAI) teaching in higher education has not been optimally implemented, particularly in integrating Islamic values ​​into real social practices. PAI learning still tends to focus on the cognitive aspect, thus providing little room for strengthening the affective dimension and providing students with direct experience in actualizing Islamic teachings. This condition results in PAI learning lacking context and failing to fully instill Islamic values ​​meaningfully. Therefore, learning innovations are needed that enable students to experience and practice Islamic values ​​directly in social life. This study aims to examine the integration of philanthropic values ​​in PAI learning through the application of the Project-Based Learning (PjBL) approach. The focus of this research is a social action project involving the distribution of food and donations to orphans at Assidiqiyah Kaliwadas Elementary School. This research uses a descriptive qualitative approach with a case study method. The subjects were students taking the PAI course in the Applied Nursing Anesthesiology Study Program at An Nasher University, Cirebon, who were directly involved in philanthropic activities. The class consisted of 28 students. Data collection techniques included participant observation, in-depth interviews with students and lecturers, and documentation of activities. The results of the study indicate that the application of Project-Based Learning (PjBL) in philanthropic activities improved students' contextual understanding of Islamic values. Students demonstrated increased empathy, social awareness, and commitment to the value of compassion in Islamic teachings. Furthermore, these activities provided a space for the actualization of religious teachings, fostering social piety as part of strengthening prophetic character. The novelty of this research lies in the integration of the Project-Based Learning approach with structured philanthropic practices in Islamic Religious Education (PAI) learning. This approach presents a contextual learning model based on real social action and offers practical implications for the development of transformative Islamic religious education in higher education.